Calcium hydroxide nanoparticles induce cell death, genomic instability, oxidative stress and apoptotic gene dysregulation on human HepG2 cells - Hanan R. H. Mohamed; Esraa H. Ibrahim; Shahd E. E. Shaheen; Nesma O. E. Hussein; Ayman Diab; Gehan Safwat (Scientific Reports)
Abstract Calcium hydroxide nanoparticles (Ca(OH)2NPs) possess potent antimicrobial activities and unique physical and chemical properties, making them valuable across various fields. However, limited information exists regarding their effects on genomic DNA integrity and their potential to induce apoptosis in normal and cancerous human cell lines. This study thus aimed to evaluate the impact of Ca(OH)2NPs on cell viability, genomic DNA integrity, and oxidative stress induction in human normal skin fibroblasts (HSF) and cancerous hepatic (HepG2) cells. Cell viability and genomic DNA stability were assessed using the Sulforhodamine B (SRB) assay and alkaline comet assay, respectively. Reactive oxygen species (ROS) levels were measured using 2,7-dichlorofluorescein diacetate, while the expression level of apoptosis-related genes (p53, Bax, and Bcl-2) were quantified using real-time PCR (qRT-PCR). The SRB cytotoxicity assay revealed that a 48-hour exposure to Ca(OH)2NPs caused concentration-dependent cell death and proliferation inhibition in both HSF and HepG2 cells, with IC50 values of 271.93 µg/mL for HSF and 291.8 µg/mL for HepG2 cells. Treatment with the IC50 concentration of Ca(OH)2NPs selectively induced significant DNA damage, excessive ROS generation, and marked dysregulation of apoptotic (p53 and Bax) and anti-apoptotic (Bcl-2) gene expression in HepG2 cells, triggering apoptosis. In contrast, exposure of HSF cells to the IC50 concentration of Ca(OH)2NPs caused no significant changes in genomic DNA integrity, ROS generation, or apoptotic gene expression. These findings indicate that Ca(OH)2NPs exhibit concentration-dependent cytotoxicity in both normal HSF and cancerous HepG2 cells. However, exposure to the IC50 concentration was non-genotoxic to normal HSF cells while selectively inducing genotoxicity and apoptosis in HepG2 cancer cells through DNA breaks and ROS-mediated mechanisms. Further studies are required to explore the biological and toxicological properties and therapeutic potential of Ca(OH)2NPs in hepatic cancer treatment.